The Dada Painters and Poets : An Anthology - Motherwell, Robert (New York : George Wittenborn, Inc., 1967)
Arp ; Clair ; Duchamp ; Eggeling ; Ernst ; Hausmann ; Janco ; Klee ; Picabia ; Richter ; Schwitters ; Stieglitz ; Taeuber-Arp etc.
Documents, Objects, Journals, Reviews, Manifestoes, Photographs, Catalogues, Invitations etc.
Engels
boek